Estudo morfoanatômico, avaliação da atividade biológica e composição química e variabilidade do óleo essencial da Memora nodosa (SILVA MANSO) Miers - Bignoniaceae - TRESVENZOL, Leonice Manrique Faustino (2008)
Memora nodosa (Silva Manso) Miers is a native savannah plant popularly used for wound cicatrization (leaves and stems) and for treating abdominal pains and scabies (roots). The purpose of this work is to study the morphoanatomy and determine the composition and variability of the constituents of the essential oil obtained from the M. nodosa leaves, as well as its antimicrobial, leishmanicidal, cicatrizing activity and toxicity. Morphologically, M. nodosa is a bush with clumps of straight or curved stems. It has a deep, pivoting root and presents a chandelier shaped structure in the upper part from where the stems sprout. It presents compound, bipinnate, imparipinnate, oppositely crossed leaves. The inflorescence is racemose with golden-yellow flowers. It is characterized by septifrague capsule type fruit with replum and winged seeds. Anatomically the leaves are hypostomatic with predominantly paracytic stomates. The epidermis is uniseriate with a thick cuticle and glandular trichomes throughout the structure of the young leaves. The essential oil from the M. nodosa leaves collected from seven different locations in the Brazilian savannah was analyzed by GC(FID) and GC/MS. Five substances were identified, benzaldehyde and 1- octene-3-ol were the main constituents. Two different classes regarding sampling location and constituents were identified by means of the principal component and grouping analyses. The antimicrobial activity of the ethanolic extracts from leaves, stems, roots and of essential oil from leaves, and the fractions obtained from the roots, were assessed against Grampositive and Gram-negative bacteria, as well as the Candida albicans fungus, using well diffusion test and the agar dilution method. The ethanolic extract from the roots presented small antimicrobial activity while the hexane and dichloromethane fractions obtained from this extract presented MIC 0.39 mg/mL and 0.78 mg/mL against a number of Gram-positive bacteria and the Candida albicans fungus. The essential oil presented MIC 0.78 mg/mL to 1.56 mg/mL. The antimicrobial activity of the essential oil was the result of synergic action between the benzaldehyde, 1-octene-3-ol, 1-octanol, linalool and the mandelonitrile, constituents of the essential oil. Promastigote forms of Leishmania chagasi were used for the leishmanicidal assessment and it was verified that the ethanol extract from the leaves presented an IC50 of 93.2 μg/mL and from the roots presented an IC50 of 95.87 μg/mL. The hexane fraction from the roots presented an IC50 of 13.51μg/mL. A mixture of β-sitosterol and stigmasterol was isolated and identified in the hexane fraction obtained from the ethanol extract from the roots. This mixture was tested against L. chagasi resulting in an IC50 of 69.79 μg/mL. The cicatrizing activity of the ethanol extract from the leaves and roots was assessed on skin wounds in rats, and it be noted reepithelization occurred faster only in the group treated with a 2% aqueous solution of the ethanol extract from the roots. This action may be related to the alantoine isolated in the ethanol extract from the roots. The toxicity assessment of the ethanol extracts from roots, leaves and hexane fraction obtained from M . nodosa roots, tested on rats, mice and Artemia salina proved that this plant is not potentially toxic. In conclusion, according to the tests performed, the best results were obtained with ethanolic extract and it presented antimicrobial, wound cicatrization and leishmanicidal activities. Hexane and dichloromethane fractions obtained from roots extract presented antimicrobial activity against Gram-positive bacteria and the Candida albicans fungus and hexane fraction strong leishmanicidal activity.